Learning agility quotient and work readiness of graduating accounting students: embracing the dynamics of IR4.0 - Azhar, Zubir; Jaludin, Dayana; K Ghani, Erlane; Ramayah, Thurasamy; Puat Nelson, Sherliza (Taylor & Francis, 2023)
This study examines if the learning agility quotient (LAQ) is an important determinant for the work readiness of graduating accounting students in the Fourth Industrial Revolution (IR4.0) environment. Using a questionnaire survey involving 275 respondents, we find that those with higher intelligence quotient (IQ) and emotional quotient (EQ) have higher LAQ. We also find that LAQ mediates the positive impact of IQ and EQ on their work readiness. Our findings implicate accounting education as they highlight the significant role of LAQ in relation to IQ, EQ, and work readiness. Further research is needed to determine if educational and work environment factors can effectively support and enhance learning agility.